A Study of Internal Factors Contributing to Marketing of Management Education in India - Bapat, Harish B. (International Journal of Psychosocial Rehabilitation, 2020)
–The present paper investigates in to the details of internal factors affecting the marketing of education. The paper plans to underline the fundamental attributes required for educational market and their manner in which they occur to the Market (target Audiences). To study the role of marketing initiatives in the domain of educational institutes is very crucial and contemporary. We could make out a differentiation between the external marketing and the intrinsically engaged marketing initiatives, on the bases of the service marketing standards, that are conventional yet moderately new in the education field. The results of the present investigation lead to the factors that influence (In relative order of significance) the decision of choosing the professional education institutes by students and their parents. The study also focuses on the investigation of the components which guardians from selected region consider significant when choosing the mentioned educational institutes.